Curricular Strategy For Public Health And Environmental Training: The Environmental Dimension In The Basic Sciences Of The Medical Studies - Rodríguez Cabrera, Ileana; Aguilera Pereira, Hilda; Vicedo Tomey, Agustín (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: In the Medical Studies, environmental education becomes an imperative for the training of this type of professional, given the relationship between environmental problems and health problems. The Environmental Education for Sustainable Development, considered as the environmental dimension of comprehensive education, must be present in all the leading documents of the curriculum since it is considered a transverse axis of these, which is related to general objectives unattainable from a single subject and / or discipline, so it must be present in the medical training curriculum. Objective: To propose a modality of inclusion of the Environmental Dimension, through the Curricular Strategy of Public Health and Environmental Training in different subjects of the Basic Sciences of the discipline known as Biological Basis of Medicine in medical studies mayor. Methods: Documents of the study plan of the Medical Studies, the discipline known as Biological Bases of Medicine and important environmental aspects are analyzed, through different theoretical methods. Results: The relationship between the environmental dimension and contents in different subjects of Basic Sciences of the discipline Biological Bases of Medicine is established. Conclusions: We propose a modality of inclusion of the environmental dimension, through the Curricular Strategy of Public Health and Environmental Training, in contents of different subjects of Basic Sciences in Biological Bases of Medicine discipline within these studies.